MENINGKATKAN HASIL BELAJAR SISWA MELALUI MEDIA DIGITAL BLOOKET PADA PEMBELAJARAN DI SEKOLAH DASAR - Putri Febriani Dunggio; Rustam I. Husain; Muhammad Sarlin; Nurainun; Candra Cuga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve student learning outcomes in Social Sciences (IPS) through the use of Blooket digital media in class V of SDN 12 Kota Barat, Gorontalo City. This study uses the Classroom Action Research (CAR) method consisting of two cycles, where each cycle includes the planning, implementation, observation, and reflection stages. The research subjects were 8 students consisting of 5 male students and 3 female students. Data were obtained through observations of teacher and student activities and learning outcome tests. The results showed an increase in student learning outcomes after the implementation of Blooket media. In the initial observation, only 25% of students achieved the KKM. In cycle I, learning completeness increased to 50%, and in cycle II it increased significantly to 88% or as many as 7 students achieved a score of ≥ 75. In addition, teacher and student activities also increased in each cycle, indicating that Blooket digital media is able to create more interactive, interesting, and motivating learning for students. Thus, it can be concluded that the Blooket digital media is effective in improving the social studies learning outcomes of fifth grade students. This media can be an innovative learning alternative and support technology-based learning in elementary schools.